SUSTAINING THE GLOBAL EDUCATION AGENDA (EDUCATION 2030): LEARNING AND BEYOND - MPRC, Pusat Media & Perhubungan Awam (USM, 2017)
USM, PENANG, 24 January 2017 – “Various countries have adopted a set of goals on September 25, 2015 in Rio as part of their involvement in the Sustainable Development Agenda. These global goals and targets are aimed to initiate action over the next fifteen years,” said the Universiti Sains Malaysia (USM) Deputy ViceChancellor (Academic and International), Professor Dato’ Dr. Ahmad Shukri Mustapa Kamal in his opening speech at the Public Lecture by Professor Charles Hopkins organised by Universiti Sains Malaysia (USM) here today.